Volatility Widens Inequality. Could Aid and Remittances Help? - Lisa Chauvet; Marin Ferry; Patrick Guillaumont; Sylviane Guillaumont Jeanneney; Sampawende J.-A. Tapsoba; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
We analyse the relationship between income volatility and inequality and the conditional role played by aid and remittances. Using a panel of 142 countries for the period 1973 to 2012, we find that income volatility has an adverse impact on inequality, and that the poorest people are the most exposed to these fluctuations. However, while aid and remittances do not seem to have a clear direct impact on inequality, we uncover robust evidence which suggests that aid helps to dampen the negative effects of volatility on the distribution of income, while remittances do not.Keywords: Volatility, Inequality, Aid, and Remittances
Keywords: F35; F24; O15; 330; Aid; Income volatility; Inequality; Remittances